ПЕДАГОГИЧЕСКИЕ УСЛОВИЯ ФОРМИРОВАНИЯ КУЛЬТУРЫ ЗДОРОВОГО ОБРАЗА ЖИЗНИ СТУДЕНТОВ (Педагогіка вищої та середньої школи, 2008)
The article deals with some problems concerning the formation of the students culture of healthy way of lift; some definitions of the theme researched; pedagogical conditions of the formation of students culture of healthy way of life.